Состояние фотосинтетических пигментов в листьях инбредных линий и гибридов кукурузы - Тютяев, Е.В.; Шутова, В.В.; Максимов, Г.В.; Раденович, Ч.Н.; Гродзинский, Д.М. (Физиология растений и генетика, 2015)
Исследовали состояние фотосинтетических пигментов в листьях инбредных линий и гибридов кукурузы. Установлено, что у инбредных линий кукурузы в отличие от гибридов сильно варьирует соотношение хл а/хл b, однако количество молекул каротиноидов, приходящихся на одну молекулу хлорофилла, сильно изменяется у гибридов, что практически не характерно для инбредных линий. Досліджували стан фотосинтетичних пігментів у листках інбредних ліній та гібридів кукурудзи. Встановлено, що в інбредних ліній кукурудзи на відміну від гібридів сильно варіює співвідношення хл а/хл b, однак кількість молекул каротиноїдів, що припадають на одну молекулу хлорофілу, сильно змінюється в гібридів, що практично не характерно для інбредних ліній. It is shown that the ratio Chl a/Chl b in the inbred lines of maize varies, what is not observed in the hybrids, however the number of molecules of carotenoids per one molecule of chlorophyll varies in hybrids while it little changes in inbreds. With Raman spectroscopy is revealed that the carotenoids in the leaves of hybrids and inbreds are predominantly in the trans configuration; significant changes in the conformation of the polyene chaіn of the molecule does not occur, however the contribution of the valence vibrations of methyl groups (especially in the hybrid ZP 341) and the spatial orientation of the atoms in the molecule vary to a large degree.